THE LAW OF PRACTICING DHAIF HADITH IN FADHAIL A'MAL - Rambe, Mgr Sinomba; Husna, Jannatul; Waharjani, Waharjani (UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
The position of hadith in Islamic law is to strengthen and elaborate the laws and rules contained in the Koran, but in this era there are still many who do not understand the types of hadith, which are strong, weak, false, and even not allowed to be practiced. Because of this, a strong and significant understanding is needed regarding the law of practicing dhaif hadiths in Fadhail al-Mal. This study aims to identify the meaning of dhaif hadith and the law of practicing it in fadhail amal in everyday life. This study combines qualitative research with literature review research. All of the data sources that the researchers surveyed included several scientific articles, library books, and other sources relevant to the law of practicing dhaif hadith in fadhail amal. The results of the study show that the law of practicing dhaif hadiths in fadhilah charities is very permissible, provided that one first understands the quality and quantity of these hadiths, both in terms of the narrators and the line of the sanad. There are types of hadiths that may be practiced, and there are also types of daif hadiths that are forbidden to be profitably practiced in charity fadhail. in the sense that a daif hadith can be used as proof and argument for a practice, provided that the level of the hadith does not belong to a shadid hadith (very weak), let alone a maudlu or fake hadith.